Induction of labour using foley catheter: traction versus non traction technique, a randomized prospective study. - Ismail, Siti Mariam; Nusee, Zalina; Ismail, Hamizah; Mohd Nor, Nurul Yaqin (2018)
Background: Cervical ripening of an unfavourable cervix can be achieved by placement of a transcervical Foley catheter. Objective: To assess the effectiveness of 750 ml traction on Foley catheter compared to no traction for labour induction. Study design: A randomized controlled trial performed on pregnant women at 37-41 week who were admitted for induction of labour with unfavourable cervix. They were randomly assigned into two groups, Foley’s with 750 ml traction and and without traction. The primary outcomes were improvement in Bishop Score, number of favourable cervix following induction and the mode of delivery. The secondary outcomes were maternal pain score, neonatal outcome, and maternal infection. Results: A total of 160 women were randomized into traction group (n=80) and non-traction group (n=80). The mean change in Bishop Score was similar in both groups. Traction group had significantly (p=0.006) higher number of vaginal delivery (70%) compared to non-traction group. The rate of successful VBAC was also significantly (p= 0.001) higher in the traction group. Participants were comfortable using both methods with low pain score. There was no difference in neonatal outcomes and risk of maternal infections in both groups. Conclusion: application of traction did result in more vaginal delivery and successful VBAC without risk of maternal and neonatal infection.